Bilateral pedicled gracilis flap for scrotal reconstruction. Issue 9 (September 2016) - Daigeler, Adrien; Behr, Björn; Mikhail, Bassem Daniel; Lehnhardt, Marcus; Wallner, Christoph
Summary: Trauma, infection and cancer can cause severe scrotal defects. The demand to a definitive reconstruction in terms of aesthetics and function is high. Primary closure, skin grafts and local fasciocutaneous flaps do not meet these high demands in most cases. The authors treated a series of patients requiring scrotal reconstruction with bilateral pedicled gracilis muscle flaps and split thickness skin grafts, resulting in satisfying aesthetic and functional outcomes.